The Concept of Sincerity in The Qur'an and its Implementation Among The Academic Community of Ma'had Aly As'adiyah Sengkang - Samsir, Samsir; Rosmini, Rosmini; Haddade, Hasyim (International Journal of Islamic Studies, 2023)
This research explores the meaning of sincerity in the Quran and its implementation within the academic community at Ma'had Aly As'adiyah Sengkang, South Sulawesi. This type of research is qualitative descriptive, with approaches involving interpretation (tafsir) and sociological analysis. The data source for this research is the academic community of Ma'had Aly in South Sulawesi. The results of this research demonstrate the concept of sincerity from the perspective of the academic community at Ma'had Aly As'adiyah Sengkang and how it aligns with the principles passed down to the founder of the As'adiyah Islamic Boarding School by Anre Gurutta KH.Muh. As'ad. The implementation of sincerity at Ma'had Aly As'adiyah Sengkang involves fulfilling the responsibilities entrusted by Anre Gurutta. Teachers should begin with themselves, setting an example by taking the initiative to do things without being told. They should be responsible for their tasks, sensitive to what needs to be done and how to do it best. They should strive to be sincere, avoid envy towards other teachers, and teach to make students knowledgeable in religion or taffakkuh fiddin. Additionally, they seek compensation before discussions.